A Needs Assessment to Inform Research and Outreach Efforts for Sustainable Agricultural Practices and Food Production in the Western United States - Alexa J. Lamm; Kevan W. Lamm; Sara Trojan; Catherine E. Sanders; Allison R. Byrd (Foods, 2023)
Increasing the adoption of sustainable agricultural practices can help maintain sufficient food production while reducing its environmental impact. To ensure this adoption, it is important to assess the research and training needs of those helping farmers and producers adopt sustainable agricultural practices. However, there is a gap in the literature related to the training needs of producers in the Western United States for sustainable agriculture. Needs assessments help organizations, such as the Western Sustainable Agriculture Research and Education (SARE) program and Cooperative Extension, to address the demonstrated needs of intended audiences. This study presents the results of a needs assessment with the objective of examining training needs and barriers to adoption to help direct extension programming for sustainable agricultural practices in the western region of the United States, to identify gaps, and to inform sustainable agriculture outreach programs. Using a modified Borich method with an inferential statistical method, the discrepancies between the level at which sustainable agricultural practice training competencies “should be addressed” and the level at which they were “currently being addressed” were examined. Competencies with the largest gaps included financial disparity, food waste, and policy/communicating with decision makers. The top three barriers to adopting sustainable agricultural practices included the potential for financial loss, perceived risk of adoption, and time investment associated with adoption. Results indicated that training needs varied and that these were not all on-farm training needs. The results imply that future funding from Western SARE and other groups looking to support sustainable agricultural food system efforts, may wish to focus on requesting proposals for programs that address these competency gaps and barriers in novel and supplementary ways in combination with existing programmatic efforts.